Refinement of the crystal structure of diaqua-(3,10-C-meso-3,5,7,7, 10,12,14,14-octamethyl-1,4,8,11-tetraazacyclotetradecane)copper(II) diperchlorate, [Cu(C18H40N4)(H2O) 2](ClO4)2, at 173 K - Hazari, S.K.S. (2014)
Zeitschrift fur Kristallographie - New Crystal Structures